Torsional fatigue mechanisms of an A357-T6 cast aluminium alloy. (December 2020) - Serrano-Munoz, I.; Shiozawa, D.; Dancette, S.; Verdu, C.; Buffiere, J.-Y.
Graphical abstract: Abstract: The mechanisms controlling the fatigue response of an A357-T6 cast aluminium alloy under cyclic torsional loading are investigated. Surface crack monitoring coupled with Electron BackScattering Diffraction (EBSD) analysis is used to study crack initiation. Determination of S-N curve combined with interrupted in situ fatigue testing using synchrotron tomography allows the study of the propagation behaviour. It is observed that fractographic morphologies depend on the stress level. At intermediate-low stress levels ( τmax  < 100 MPa), the grain structure controls the crack initiation and propagation periods. Cracks are usually nucleated in mode II from slip planes close to the specimen axis or perpendicular to it. Mode II crack growth dominates the early stages of crack propagation as mode III inward crack growth is rapidly decelerated. This behaviour leads to the formation of characteristic shallow surface cracks. Once the crack is long enough for the mode II driving force to be overtaken by mode III, propagation branches into  ~ 45 ∘ mode I.